2015
DOI: 10.1016/j.ejon.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a brain tumour website

Abstract: ISRCTN22038059.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…They appear more concerned with the ultimately progressive course of the disease, and cognitive problems that may cause them to need help using this system. Similar difficulties have been found in other eHealth initiatives for glioma patients [ 31 ]. Because of these specific difficulties, implementing a monitoring system may be less suitable in this patient population.…”
Section: Discussionsupporting
confidence: 79%
“…They appear more concerned with the ultimately progressive course of the disease, and cognitive problems that may cause them to need help using this system. Similar difficulties have been found in other eHealth initiatives for glioma patients [ 31 ]. Because of these specific difficulties, implementing a monitoring system may be less suitable in this patient population.…”
Section: Discussionsupporting
confidence: 79%
“…The preference for a blended care option corroborated findings from studies among cancer patients in general [21] and neuro-oncology patient/caregiver populations in particular [22]. Cancer survivors (N = 212) viewed eHealth applications favorably, with 48% indicating that they would find the option to self-monitor their side-effects and symptoms attractive [21].…”
Section: Discussionsupporting
confidence: 63%
“…Cancer survivors (N = 212) viewed eHealth applications favorably, with 48% indicating that they would find the option to self-monitor their side-effects and symptoms attractive [21]. A feasibility study testing a Danish brain tumor website among brain tumor patients and caregivers furthermore showed that especially caregivers appreciated the option to contact health care professionals online [22]. However, our report focuses on caregivers' preferences for keeping track of their own care issues over time-which is, indeed, a relatively unexplored area [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…There are several tele-health formats (e.g., telephone, Skype, video-conferencing, Internet-based resources); hence, there is a need to take into account people's sensory-perceptual, motor, language and cognitive functioning as well as their familiarity with technology, particularly for computer-mediated support. Pilot research into the feasibility of an interactive brain tumour-specific website by Piil, Joakobsen, Juhler and Jarden (2015) found that the website had relatively low levels of use by people with brain tumour. Interviews identified a major theme of ‘challenges and barriers’ whereby people who were newly diagnosed often felt too overwhelmed by the change in their life situation to use the online resource.…”
Section: Pilot Intervention Research and Future Directionsmentioning
confidence: 99%